The effect of catchment soils on heavy metal concentrations in a brook situated in the historic mining region of Braubach, Germany - Hahn, Jens; Zitzer, Nina; Laufenberg, Gabriela (DIE ERDE – Journal of the Geographical Society of Berlin, 2018)
Forest soils located in the region of Braubach (Rhineland-Palatinate, Germany) are characterized by elevated concentrations of cadmium (Cd), copper (Cu), and lead (Pb), resulting from local heavy metal emissions. The regional geomorphology is dominated by the low mountain range of the Rhenish Massif and the frequent occurrence of V-shaped valleys crossed by small tributaries of the Rhine River. The frequent occurrence of steep valley slopes should theoretically facilitate the influence of polluted forest soils on brooks of the valley bottoms by intensified processes of slope water influx and soil erosion. To investigate pollution state and soil-water interactions in a heavy metal enriched catchment, concentrations of Cd, Cu, and Pb were determined for catchment soils, sediment, suspended matter, and surface water of a brook situated close to a former smelter area. Heavy metal binding was characterized by BCR sequential extraction method. Total concentrations of Cd increased with the transition from catchment soils to brook sediments and suspended matter, while the proportions of the analyzed binding fractions partially changed. The concentrations of Cu and Pb in soils were marked by a higher heterogeneity and exceeded the concentrations found in sediments and suspended matter. For Pb, the proportions of binding fractions were relatively static, whereas the Cu binding fractions in suspended matter clearly differed in comparison with soils and sediments. For all studied heavy metals, an increase in the concentration of the respective dissolved fraction was found along the course of the brook.